2009
DOI: 10.1071/mf08356
|View full text |Cite
|
Sign up to set email alerts
|

Flood water quality and marine sediment and nutrient loads from the Tully and Murray catchments in north Queensland, Australia

Abstract: Abstract. Current estimates of sediment and nutrient loads from the Tully-Murray floodplain to the Great Barrier Reef lagoon are updated by taking explicit account of flood events. New estimates of flood discharge that include over-bank flows are combined with direct measurements of sediment and nutrient concentrations in flood waters to calculate the loads of sediment and nutrient delivered to the ocean during 13 floods that occurred between 2006 and 2008. Although absolute concentrations of sediment and nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 7 publications
2
56
0
Order By: Relevance
“…During flood events in the Tully River, nitrate concentrations rise with increasing discharge to a broad peak between 10 000 and 40 000 ML day −1 , beyond which higher discharge leads to falling nitrate concentrations (Mitchell et al 2007). Wallace et al (2009) showed that over-bank floods in the Tully River occurred at discharges greater than 40 000 ML day −1 and that these floodwaters had low concentrations of nitrate, but relatively high concentrations of DON. Hence, it appears that dilution of nitrate commences at a discharge of ∼10 000 ML day −1 , whereas beyond 40 000 ML day −1 further reduction occurs when the waters flood over onto the broader coastal plain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During flood events in the Tully River, nitrate concentrations rise with increasing discharge to a broad peak between 10 000 and 40 000 ML day −1 , beyond which higher discharge leads to falling nitrate concentrations (Mitchell et al 2007). Wallace et al (2009) showed that over-bank floods in the Tully River occurred at discharges greater than 40 000 ML day −1 and that these floodwaters had low concentrations of nitrate, but relatively high concentrations of DON. Hence, it appears that dilution of nitrate commences at a discharge of ∼10 000 ML day −1 , whereas beyond 40 000 ML day −1 further reduction occurs when the waters flood over onto the broader coastal plain.…”
Section: Discussionmentioning
confidence: 99%
“…Further reductions occur over the coastal plain during bank overflows (Wallace et al 2009). These factors raise the issue of scaling of the subcatchment areas sampled and the extrapolation of measurements from small areas to the whole catchment.…”
Section: Concentration (µG Lmentioning
confidence: 99%
“…Recent research has identified that over-bank flows in the Tully-Murray that are not measured by the Euramo gauging station can contribute extra volumes of water, sediment and nutrient to the GBR (Wallace et al 2009). These additional loads may result in an underestimate by gauging of the annual average N load of ∼40-75% and the P load of ∼30-50%.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the Tully catchment, Wallace et al (2009) showed that a large proportion of the total load of suspended sediment and nitrogen was present in waters in overbank flow on the floodplain and this was not included in the load calculation made at the gauging station (Euramo) in the river channel. Similarly, it is clear that much of the nitrate lost from sugarcane fertiliser in the lower Burdekin reaches the GBR via small stream discharge and possibly groundwater discharge and is thus not included in loads measured at Home Hill in the Burdekin River (Brodie and Bainbridge 2008).…”
Section: Target Setting For the Tully-murray Basin For Nitratementioning
confidence: 99%